La literatura infantil, una experiencia estética para los niños en los primeros años de básica primaria (2017)
The present research called, Children's literature, an aesthetic experience for children in the first years of elementary school. It is developed around the concept of literature aesthetics, which aims to teach literary enjoyment through the approach to children's literature in children of the third grade of the Institution Educative Departmental Sabio Mutis, in the municipality of Mesa Cundinamarca.